Microbiology of thermally preserved foods : canning and novel physical methods - Deák, Tibor (DEStech Publications, 2013)
"Offers a practical introduction to understanding, preventing and destroying microbe-based hazards in food plants that use thermal processes to preserve and package foods. The text surveys major spoilage and pathogenic microbes of interest, explaining their toxicity, product and safety effects, and the conditions of their destruction by heat treatment"--Publisher.
Keywords: Food -- Microbiology.; Canned foods -- Microbiology.; Canning and preserving -- Microbiology.; Food -- Preservation.; Food spoilage.; Heating.; elektronické knihy; electronic books